Peran Employee Green Behavior Dalam Memediasi Green Human Resource Management Terhadap Employee Green Perfomance - Ajizah, Nur; Adriani, Zulfina; Wediawati, Besse (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of green human resource management on employee green behavior and employee green performance, as well as to explore the mediating role of employee green behavior in the relationship between green human resource management and employee green performance. The research employed a quantitative approach using a survey method, with questionnaires distributed to 90 employees at the Environmental Agency of Jambi Province. The collected data were analyzed using the Partial Least Squares (PLS) method with the help of SmartPLS software. The research results indicate that green human resource management has a significant impact on employee green behavior. Additionally, green human resource management also has a significant direct effect on employee green performance. Employee green behavior has been shown to significantly affect employee green performance. Furthermore, employee green behavior acts as a mediator, significantly mediating the relationship between green human resource management and employee green performance.